2020
DOI: 10.1159/000505613
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Effect and Safety Observation of Regional Citrate Anticoagulation for Double-Filtration Plasmapheresis in Critical Patients

Abstract: Introduction: Double-filtration plasmapheresis (DFPP) is a semi-selective blood purification method based on dual filtration system. Regional citrate anticoagulation (RCA) is an appealing anticoagulation alternative in DFPP. However, there are still few reports on the safety of RCA in DFPP treatment. Objective: To investigate the anticoagulation effect and safety of RCA for DFPP in critical patients. Methods: A total of 34 critical patients treated with DFPP were retrospectively studied. The incidence of coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 24 publications
2
19
2
Order By: Relevance
“…Maintaining circuit patency is critical for the delivery of extracorporeal therapies since it facilitates the delivery of the prescribed treatment and reduces the risk of complications, unnecessary nursing workload, and treatment cost [8]. Similar to a previous study in non-KTx patients, our study demonstrated that RCA could maintain circuit patency during DFPP, and most sessions were completed without circuit clotting [7]. Suboptimal post-filter iCa and dysfunctional vascular access likely contributed to circuit clotting in our study.…”
Section: Discussion/conclusionsupporting
confidence: 81%
See 2 more Smart Citations
“…Maintaining circuit patency is critical for the delivery of extracorporeal therapies since it facilitates the delivery of the prescribed treatment and reduces the risk of complications, unnecessary nursing workload, and treatment cost [8]. Similar to a previous study in non-KTx patients, our study demonstrated that RCA could maintain circuit patency during DFPP, and most sessions were completed without circuit clotting [7]. Suboptimal post-filter iCa and dysfunctional vascular access likely contributed to circuit clotting in our study.…”
Section: Discussion/conclusionsupporting
confidence: 81%
“…Suboptimal post-filter iCa and dysfunctional vascular access likely contributed to circuit clotting in our study. Although the achieved postfilter iCa was not reported by Peng et al [7], the lower citrate dose used in our study may have also contributed to higher rates of circuit clotting.…”
Section: Discussion/conclusioncontrasting
confidence: 59%
See 1 more Smart Citation
“…DFPP, a selective form of therapeutic apheresis, is used to treat several pathological conditions that are mainly related to autoimmune disorders 16 . The main side effect of DFPP is the risk of bleeding induced by the loss of coagulation factors 12‐15,17 . To decrease the depletion of coagulation factors, we hypothesized that changing the initial filter that is used to separate blood cells from the plasma (Plasmaflo OP‐08W) with a filter with a smaller‐pore diameter (Cascadeflo EC‐50W) would retain plasma components with a molecular weight greater than ~150 kDa 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The second filter (Cascadeflo EC‐30 W), which would make it possible to treat the plasma, was the same type in both treatment groups. The regional citrate anticoagulation used is safe and allows effective anticoagulation of the extracorporeal circuit of DFPP 15 …”
Section: Discussionmentioning
confidence: 99%